The impact of child support payments on the labour supply decisions of resident mothers - Gray, M; Taylor, M (My University, 2009)
The paper examines the effect of child support payments on separated mothers' employment. Using data from the first two waves of Growing Up in Australia, the Longitudinal Study of Australian Children (LSAC), the paper analyses the likelihood of employment of resident mothers and the number of hours worked if employed. Economic theory suggests that receipt of non-labour market income - such as child support payments - will reduce the labour force participation of mothers. However, the analysis found that the amount of child support received does not affect the likelihood of being in paid employment, though receiving larger amounts of child support - in excess of $100 per fortnight - is estimated to reduce the number of hours worked per week.
Keywords: Beliefs and Values -- Neighbourhood; Beliefs and Values; Identity; Beliefs and Values; Neighbourhood; Identity